ITRAQ-based proteomic analysis of rice seedlings' resistance induced by Streptomyces JD211 against Magnaporthe oryzae. Issue 1 (31st December 2022) - Wei, Lei; Shao, Zhengying; Fu, Yanhui; Li, Zhang; Ni, Guorong; Cheng, Xin; Wen, Yangping; Wei, Saijin
ABSTRACT: Streptomyces JD211 induces rice resistance and reduces the disease index of rice blast. However, the key pathways or components involved in the defense mechanism by which antagonistic microorganisms cause resistance have not been elucidated. To better understand the cellular process involved in JD211-induced resistance, the changes of proteomics in the rice treated with JD211 and Magnaporthe oryzae were investigated. Most proteins associated with porphyrin and chlorophyll biosynthesis decreased in M. oryzae -infected rice, whereas these proteins increased in the rice treated with JD211. Proteins increased by JD211 were also involved in the phenylpropanoid pathway, signal transduction, and ascorbate biosynthesis. These results indicated that JD211 could protect rice from M. oryzae damages by promoting signal transduction and inducing the production of phenylpropanoids. JD211 contributed to energy synthesis for defense responses in plants, reduced the damage of M. oryzae, and improved the rice resistance by inducing an array of defense responses more quickly and efficiently in the rice. The obtained data provide not only important information for understanding the molecular mechanism involved in JD211-induced resistance but also application clues for genetic breeding of crops with the improved M. oryzae resistance.